Metabolic Engineering of Extremophilic Bacterium Deinococcus radiodurans for the Production of the Novel Carotenoid Deinoxanthin - Sun-Wook Jeong; Jun-Ho Kim; Ji-Woong Kim; Chae Yeon Kim; Su Young Kim; Yong Jun Choi (Microorganisms, 2020)
Deinoxanthin, a xanthophyll derived from Deinococcus species, is a unique organic compound that provides greater antioxidant effects compared to other carotenoids due to its superior scavenging activity against singlet oxygen and hydrogen peroxide. Therefore, it has attracted significant attention as a next-generation organic compound that has great potential as a natural ingredient in a food supplements. Although the microbial identification of deinoxanthin has been identified, mass production has not yet been achieved. Here, we report, for the first time, the development of an engineered extremophilic microorganism, Deinococcus radiodurans strain R1, that is capable of producing deinoxanthin through rational metabolic engineering and process optimization. The genes crtB and dxs were first introduced into the genome to reinforce the metabolic flux towards deinoxanthin. The optimal temperature was then identified through a comparative analysis of the mRNA expression of the two genes, while the carbon source was further optimized to increase deinoxanthin production. The final engineered D. radiodurans strain R1 was able to produce 394 ± 17.6 mg/L (102 ± 11.1 mg/g DCW) of deinoxanthin with a yield of 40.4 ± 1.2 mg/g sucrose and a productivity of 8.4 ± 0.2 mg/L/h from 10 g/L of sucrose. The final engineered strain and the strategies developed in the present study can act as the foundation for the industrial application of extremophilic microorganisms.